The handbook of continuing professional development for the health IT professional - Klinedinst, JoAnn (New York : Productivity Press, 2021)
Health Information and Technology Engaging in on-going, continuing professional development (CPD) is a strategic imperative for the health informatics professional. In our global economy, healthcare is fast-paced, dynamic, and ever-changing. While this rapid change is both exciting and exhausting, digital health transformation is positively impacting lives, today and every day, in ways not previously imagined. Faced with a COVID-19 pandemic that has forever changed the landscape of health and care delivery, global health and care stakeholders must ensure that our ecosystem continues to rapidly evolve through innovation, government and ministry incentives, and technological advancements to reach citizens everywhere. For these reasons, health informaticists must embrace lifelong learning to ensure they have the professional competencies to advance initiatives that positively impact patient care. The Handbook of Continuing Professional Development for the Health Informaticist, 2nd edition, has adapted to the evolving needs of health and care professionals everywhere. The Handbook provides the rationale and the resources to do so and serves as a reference to enhance one's career. No other comprehensive resource exists to assist health informaticists in developing and maintaining their professional competencies. Written as a contributed compilation of topics by leading practitioners, The Handbook discusses the most critical competencies needed to ensure understanding of the vast health and care ecosystem while also highlighting industry influences that shape the very evolution of health information and technology.
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics -- Employees -- Training of; Performance; Career development; MEDICAL / Hospital Administration & Care; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Information Management